HUBUNGAN POLA KONSUMSI GARAM DAN KEJADIAN HIPERTENSI PADA LANSIA: TINJAUAN SISTEMATIS - Meta Zulyati Oktora; Mayang Dinda Putri; Amelia Az Zahra (Nusantara Hasana Journal, 2024)
Background: Hypertension is a major non-communicable disease and one of the leading causes of death worldwide, affecting approximately 22% of the global population. It is often called the "silent killer" because it develops asymptomatically and can cause fatal outcomes. Elderly individuals are particularly vulnerable due to physiological changes, including reduced vascular elasticity and decreased taste sensitivity, leading to excessive salt consumption in their diet. Objectives: This systematic review aims to evaluate the relationship between salt consumption patterns and the incidence of hypertension in the elderly population. Methods: A systematic review was conducted following PRISMA guidelines. Relevant studies were identified through Google Scholar and PubMed using the keywords "hypertension," "elderly," and "salt consumption" within a publication range of 2018 to 2023. Inclusion and exclusion criteria were applied to screen and select studies. A total of 12 studies meeting the criteria were analyzed. Results: Most studies reported a significant association between excessive salt consumption and hypertension among the elderly. For example, one study found that 56.7% of elderly respondents consumed salt beyond the normal range, with 54.9% of them suffering from hypertension (p=0.012). Another study reported that elderly individuals with high salt intake had a 5.704 times greater risk of developing hypertension compared to those with low salt intake (p=0.010). These findings highlight the significant impact of excessive salt intake on hypertension risk in older adults. Conclusions: Excessive salt consumption is a significant risk factor for hypertension in the elderly, driven partly by reduced taste sensitivity. These findings underscore the importance of dietary interventions and public health strategies to educate and promote low-salt diets among older adults to mitigate hypertension risk.